KONTRIBUSI PERMAINAN DALAM MEDIA AUDIO VISUAL DI MASA PAMDEMI PADA PESERTA DIDIK. - Loisa, Irena; Triansyah, Andika; Haetami, Mimi (Universitas Tanjungpura, 2023)
The problem the researcher wants to uncover and find is to find out theContribution of Traditional Games in Audio Visual Media During thePandemic for Students of Santo Benedict Pahauman Middle School.The purpose of this research is where the researcher wants to revealand find that to find out the Contribution of Traditional Games inAudio Visual Media During the Pandemic. This research is aquantitative descriptive research, meaning that it is a research that isused to find out the actual situation based on the results of a valid andreliable questionnaire instrument and a survey method. Answers fromrespondents can be made with the highest score of